Analisis Pengaruh Kualitas Aplikasi Pubg Mobile di Jayapura Menggunakan Metode Servqual - Yoo, Gonza; Emy L. Tahuhey (An Nafi': Multidisciplinary Science, 2025)
This study aims to analyze the impact of PUBG Mobile application quality in Jayapura using the SERVQUAL method. The SERVQUAL method measures five dimensions of service quality: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. A questionnaire with 20 items was distributed to 33 active PUBG Mobile users in Jayapura to serve as the research instrument. The collected data were analyzed using SPSS with multiple linear regression analysis. The results indicate that the dimensions of Tangibles, Assurance, and Responsiveness have a significant impact on the quality of the PUBG Mobile application. Specifically, the Tangibles dimension showed a positive average GAP value of 0.31, Assurance 0.27, and Responsiveness 0.13. This suggests that users' perceptions of these three dimensions exceeded their expectations, contributing significantly to the application's quality. Conversely, the Reliability and Empathy dimensions did not show a significant effect, despite having positive GAP values (Reliability 0.08 and Empathy 0.05). The study concludes that the application's reliability, assurance, and responsiveness play a key role in enhancing the user experience. Therefore, it is recommended that PUBG Mobile developers improve the application's performance in terms of stability, responsiveness, visual aspects, and system security to maximize user satisfaction. Although the Empathy dimension had the smallest GAP value, it indicates room for improvement in user interaction and emotional engagement. Therefore, it is recommended that the developers of PUBG Mobile enhance the application’s performance in terms of stability, responsiveness, visual aspects, and system security to maximize user satisfaction. Although the Empathy dimension has the smallest GAP value, it still indicates room for improvement in user interaction and emotional engagement.